Sikap Masyarakat Lokal Terhadap Pengembangan Desa Wisata Taro, Kecamatan Tegallalang, Kabupaten Gianyar - Philipus Wangku; Saptono Nugroho (JURNAL DESTINASI PARIWISATA, 2022)
Taro is the one tourism village In Tegallalang subdistric, Gianyar Regency. In the development ofBali tourism, there ia saturation of moderen forms of tourism and want to feel and life in rudal areasmaking the development of tourism in rural areas which Will be packaged in the form of tourism.Tourism Villages in Bali have not all gone smoothly so that they still need help from stakeholder in termsof developing at tourist village. Taro village ia one of the tourist village that has a variety of wonderfulpotential in the form of attraction, as well as tourist attractions. The porpuse of this study was todetermine the existing conditions in Taro tourism village, Tegallalalng sub distric, and to find out theattitude of the local comunity in developing Taro tourism village, Tegallalalng sub distric.The research methodology used in this study ia qualitative research where this qualitative researchuses observation techniques, in depth interview and documentation studies. And using the concept of 4Atourism produce, components in formulating the existing condition of Taro tourism village.The result of the study show that the existing condition of Taro tourism village starting fromattractions, accessibility, fasilitas, and tourism supporting institutions are still in the developmentproccess, so that is requires collaboration between stakeholder d in developing Taro tourism village, andattitude of local comunities in developing Taro tourism village with using the irridex ( Irritation index)concept.Keywords: comunity attitudes, developing villages (irridex), tourism village.